An assessment of the performance of licensed dental technicians in the armed forces of the Philippines - Soriano, Carolina S. (Manila College of Public Health, University of the Philippines Manila, 2018)
The study "An Assessment of the Performance of Licensed Dental Technicians in the Armed Forces of the Philippines was to determine the effectiveness of the training for dental technicians of the Armed Forces of the Philippines The Dental Service Training School is a recognized training institution by the Technical Skill Development Authority (TESDA) which equips the trainees with high level of skills to perform the function of a professional dental technician.
The researcher used Survey Questionnaire, Focus Group Discussion, and Key Informant Interview to gather data that was conducted last October 17. Originally, the researcher targeted 169 respondents but due to the nature of their assignment as soldier in the Armed Forces, none of them are indispensable and can be transferred to other units of the AFP. Forty four (44) are based in the National Capital Region. Unfortunately, only 14 respondents were captured. According to the gathered data, most of the respondents believed that the training being administered by the Dental Service Training School reinforces them to continue practicing their knowledge and skill as a licensed dental technician.
Includes appendices and references.
Special Study
Keywords: Dental technicians -- Performance -- Philippines -- Military personnel; Dental care -- Military personnel -- Philippines; Armed Forces of the Philippines -- Dental service